Avaliação do índice de radiação ionizante natural e exposição solar na região de Araçatuba-SP - Fernandes, Marco Antonio Rodrigues [UNESP]; Nagamatsu, Rafael Yukio; Castelli, Natália Cristina; Nascimento, Marcos Vinicius; Lima, Franciane Martins de; Flavis, Jéssica Matiello de; Valadão, Bruno; Vieira, Silvair Rodrigues; Kadri, Natalya Gonçalves (My University, 2011)
The work analyzes the measures of the index of ionization radiation natural (backgroung - BG) and the density rate of solar energy incidents in the Araçatuba-SP region, verifying the influences of climatic and local region variables in the parameters of calculations used in the procedures of radiation dosimetrics. It is encouraged on the increase of the occurrence of skin tumors in function of the indexes of incident ultraviolet radiation. It intends to show that the study about radiations can be focused in the initial courses of the exact sciences, and to illustrate the importance of the researches in the field of the radiations and their biological effects. The experimental measures were accomplished with three different radiation detectors, and equipments of verification of the atmospheric pressure, temperature, relative humidity of the air and potency density of the solar rays incidence, in points of interest in the Araçatuba-SP region. The results compare the experimental values with those determined mathematically by the Torricelli equation studied in physics disciplines. For the medium density of potency of the solar incidence was the value of 271,57 W/m². The atmospheric pressure (P) average measured was of 725,003 mmHg, corresponding to the relative humidity of the air of 69,56%. In terms of background radiation it was obtained the medium value of 0,024 mR/h. The value of pressure experimentally measured presents a deviation of about 1,0% in relation to the foreseen mathematically. The work contributed to motivate the students of the engineering courses to they continue his the development of researches in the area of the radiological physics, this can be confirmed by the students' participation in works presented in congress of the area.

O trabalho analisa as medidas do índice de radiação ionizante natural (background - BG) e taxas de densidade de energia solar incidentes na região de Araçatuba-SP verificando a influência de variáveis climáticas e loco-regionais nos parâmetros de cálculos utilizados nos procedimentos de dosimetria das radiações. Atenta-se sobre o aumento da ocorrência de tumores de pele em função dos índices de radiação ultravioleta incidente. Pretende-se mostrar que o estudo sobre radiações pode ser focado nos cursos iniciais das ciências exatas, e ilustrar a importância das pesquisas multiprofissionais no campo das radiações e seus efeitos biológicos. As medidas experimentais foram realizadas com três diferentes detectores de radiação, e equipamentos de verificação da pressão atmosférica, temperatura, umidade relativa do ar e densidade de potência da incidência de raios solares, em pontos de interesse na macrorregião de Araçatuba-SP. Os resultados comparam os valores experimentais com aqueles determinados matematicamente pela equação de Torricelli estudada nas disciplinas de física. Para a densidade média de potência da incidência solar encontrou-se o valor de 271,57 W/m². A pressão atmosférica (P) média medida foi de 725,003 mmHg, correspondendo à umidade relativa do ar de 69,56%. Em termos de radiação de fundo obteve-se o valor médio de 0,024 mR/h. O valor de P medido experimentalmente apresenta um desvio de cerca de 1,0% em relação ao previsto matematicamente. O trabalho contribuiu para incentivar os estudantes dos cursos de engenharia a continuarem o desenvolvimento de pesquisas na área da física radiológica, isto pode ser confirmado pela participação dos alunos em trabalhos apresentados em congressos da área.
Evaluation of the index of natural ionizaton radiation and sola exhibition in the region of the Araçatuba-SP
Keywords: Radiation; Skin cancer; Dosimetry; Pressure atmosphere; Araçatuba; Radiação; Câncer de pele; Dosimetria; Pressão atmosfera; Araçatuba